Mechanical generation of spin current - Matsuo, Mamoru; Ieda, Junichi; Maekawa, Sadamichi (Frontiers in Physics, 2015)
We focus the recent results on spin-current generation from mechanical motion such as rigid rotation and elastic deformations. Spin transport theory in accelerating frames is constructed by using the low energy expansion of the generally covariant Dirac equation. Related issues on spin-manipulation by mechanical rotation are also discussed.